Chimney Graft Technique Combined With Embolization for Treating Ruptured Aortic Arch Lesions - Bao, Xianhao; Zhao, Yuxi; Li, Tao; Wu, Mingwei; Zeng, Zhaoxiang; Gao, Minxin; Xu, Ding; Feng, Jiaxuan; Feng, Rui (Frontiers in Cardiovascular Medicine, 2021)
Background: This study aimed to share the experience in applying chimney graft technique combined with embolization for treating aortic arch rupture under emergency conditions and evaluating early-term results in these patients. Methods: This study retrospectively included patients with ruptured aortic arch lesions who received the chimney graft technique combined with embolization between March 2016 and March 2021. The primary endpoint was a technical success, deemed as successful stent graft deployment to the planned location, patency of the target branch vessel, and absence of significant type I endoleak. The secondary endpoint was clinical success defined with the size of false lumen in follow-up remaining unchanged or decreasing over time, 30-day mortality, complication, and primary patency of chimney graft. Results: This study included 12 patients (age, 61 ± 12 years; male, 83%). Five patients (42%) received single-chimney, one patient (8%) received double-chimney, and six patients (50%) received triple-chimney. Intraoperative type I endoleak occurred in six patients (50%) who underwent endovascular embolization in the primary operation. Postoperative type I endoleak, evaluated by computed tomography angiography examination following the primary operation, occurred in seven patients (58%), including one patient who received endovascular embolization two times. All patients with postoperative type I endoleak were successfully re-treated using coil and Onyx glue within one week, and the median length of stay was 22 ± 11 days (range: 7-44 days). Overall technical success was 100%. Eleven patients had completed their follow-up (median, 12 months, range: 1-34 months), and one patient was out of contact. The 30-day mortality was 9% (1/11, postoperative death of a patient with cerebral hemorrhage). No major complications and no chimney compression, migration, occlusion, or stenosis were recorded during follow-up. Seven patients (58%) have ≥6 months of clinical follow-up time with appropriate imaging. In four (57%) of these patients, diameter stabilization was detected, whereas three (43%) experienced significant reduction (≥5 mm). Conclusion: The patients in this study had satisfactory early-term outcomes. The chimney graft technique combined with coil and Onyx glue embolization may be a safe and effective treatment of ruptured aortic arch lesions under emergency conditions.